First report on microcystins contamination in giant freshwater prawn (Macrobrachium rosenbergii) and Nile tilapia (Tilapia nilotica) cultured in earthen ponds - Khomsan Ruangrit (2018)
Phytoplankton including cyanobacterial blooms frequently occurred in aquaculture ponds. Some cyanobacteria produced toxins that may accumulate in the food web and eventually to aquaculture products. The aim of this study was to investigate the incidence of cyanobacteria and the contamination of microcystins in giant freshwater prawn (Macrobrachium rosenbergii) and Nile tilapia (Tilapia nilotica) cultured in earthen ponds. This study was carried out in green water system of 4 prawn and 6 fish ponds during April 2006 - February 2007. Cyanobacterial composition was identified by microscopic method and microcystins were analyzed by ELISA technique. It was shown that the amount of cyanobacteria especially Microcystis aeruginosa Kützing (n.d.-45,000 cells/L) and microcystins (n.d.-3.20 μg/kg d.w.) in the prawn ponds was higher than that in fish ponds (n.d.- 983 cells/L & n.d.-0.84 μg/kg d.w.). Both prawn and fish contained concentrations of microcystins close to or above the recommended limit for human consumption (0.04 μg/kg day TDI guidelines set by the WHO). This result implied that aquaculture products especially giant freshwater prawns cultured in earthen ponds with green water system are likely to be contaminated with microcystins. The finding is useful for aquaculture in term of food safety in Thailand. © 2011 Friends Science Publishers.